What did you eat yesterday? 14 - Yoshinaga, Fumi, 1971- (Kodansha USA Publishing, LLC, 2019)
"Shino and Shuhei deal with busybodies worried about their health. Tabuchi figures out how make his latest girlfriend try new things in the kitchen. Shiro and Kenji meet up with Kohinata and Wataru to ring in the new year... but as the quartet of friends get older they learn to be more practical in their celebrations. And Kenji's boss makes a surprising decision for the future of the salon."--Provided by publisher.